SOCIAL NEUROSCIENCE: THE MARRIAGE BETWEEN SOCIAL PSYCHOLOGY AND COGNITIVE NEUROSCIENCES. A REVIEW AND AN INTRODUCTION TO A NEW DISCIPLINE. - Grande-García, Israel (Anales de Psicología / Annals of Psychology, 2009)
Social neuroscience is a new discipline emerging from the com-bination of the research in social psychology and cognitive neurosciences whose aim is the study of the biological foundations (immune, endocrine, neural) of social cognition and behavior, combining the most advance tools of cognitive neuroscience as neuroimaging and neuropsychology, along with the research in cognitive sciences and social sciences as social psychology, economics and political sciences. This paper makes an histori-cal introduction and a review of the main subjects of social neuroscience: social perception (perception of faces, bodies and actions); theory of mind; understanding other’s emotions; self-consciousness (self-recognition, sense of agency and sense of ownership, self-reflection, self-concept, autobiographical memory); self-regulation; attitudes and preju-dices; and social rejection.